The frequency of breakfast consumption among undergraduate students of nursing and dietetic programme / Noor Athirah Che Alek, Nur Nadzira Bahiah Mohd Jaffare and Nur Syazwani Awang Ngah - Che Alek, Noor Athirah; Mohd Jaffare, Nur Nadzira Bahiah; Awang Ngah, Nur Syazwani (2016)
Background: Breakfast skipping is relatively common among students whether primary school students, secondary school students and university students. The common reasons that hindered from taking breakfast are lack of time and lethargy due to lack of sleep because of study. Skipping breakfast also can effect body weight and reduced physical activity. Objective: Aim of this study to determine the frequency of breakfast consumption among undergraduate students of Nursing and Dietetic Programme. Method: Cross-sectional study was conducted at UiTM Puncak Alam. The data were collected using adapted questionnaire on Breakfast Habit, Believes and Measures of Health and Well-being. A total of 171 (ni= 86 and m= 85) respondents consist of nursing and dietetic students were participated in this study. Participants answered complete set of questionnaire within 15 minutes time. The data was analysed and interpret using Descriptive statistic, Mann Whitney and Pearson Correlation Chi Square.